2014
DOI: 10.1016/j.eucr.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy for the Treatment of Renal Tumors

Abstract: The purpose of this study was to evaluate the response of actively growing renal masses to stereotactic body radiation therapy (SBRT). We retrospectively reviewed our institutional review board–approved kidney database and identified 4 patients who underwent SBRT, 15 Gy dose, for their rapidly growing renal masses. Three patients had a decreased tumor size after radiation treatment by 20.8%, 38.1%, and 20%. The other patient had a size gain of 5.6%. This patient maintained a similar tumor growth rate before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Clinically, a wide range of SBRT fractions (1–10) and doses (18 to 60 Gy) for inoperable RCC have been reported in the literature (29). In this study, 15 Gy in 1 fraction was utilized due to 3 factors: 1) clinical experience with this dose being well tolerated in our inoperable patients (18), 2) radiobiological data suggesting vascular effects with this dose (30), and 3) in vitro experiments (Fig. 1) showing that this dose has immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinically, a wide range of SBRT fractions (1–10) and doses (18 to 60 Gy) for inoperable RCC have been reported in the literature (29). In this study, 15 Gy in 1 fraction was utilized due to 3 factors: 1) clinical experience with this dose being well tolerated in our inoperable patients (18), 2) radiobiological data suggesting vascular effects with this dose (30), and 3) in vitro experiments (Fig. 1) showing that this dose has immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…This dose was chosen based on our recent experience with this treatment being well tolerated in inoperable renal cell carcinoma patients (18). Patients were followed for protocol related toxicity 30 ± 3 days following surgery or until resolution of any toxicity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 48 Several retrospective studies have reported outcomes of single-fraction SBRT to the kidney. Hanzly et al 49 retrospectively evaluated 4 patients who were prescribed 15 Gy × 1 fraction for rapidly growing renal masses without histologic confirmation. Three of the 4 patients had tumor size reduction (average 0.85 cm) at 13.8 months follow-up.…”
Section: Methodsmentioning
confidence: 99%